Tumor-associated macrophages in oral premalignant lesions coexpress CD163 and STAT1 in a Th1-dominated microenvironment - Mori, Kazumasa (BMC Cancer, 2015)
BACKGROUND: Tumor-associated macrophages (TAMs) are implicated in the growth, invasion and metastasis of various solid tumors. However, the phenotype of TAMs in premalignant lesions of solid tumors has not been clarified. In the present study, we identify the phenotype of TAMs in leukoplakia, an oral premalignant lesion, by immunohistochemical analysis and investigate the involvement of infiltrated T cells that participate in the polarization of TAMs. METHODS: The subjects included 30 patients with oral leukoplakia and 10 individuals with normal mucosa. Hematoxylin and eosin slides were examined for the histological grades, and immunohistochemical analysis was carried out using antibodies against CD68 (pan-MΦ), CD80 (M1 MΦ), CD163 (M2 MΦ), CD4 (helper T cells: Th), CD8 (cytotoxic T cells), CXCR3, CCR5 (Th1), CCR4 (Th2), signal transducer and activator of transcription (STAT1), phosphorylated STAT1 (pSTAT1) and chemokine CXCL9. The differences in the numbers of positively stained cells among the different histological grades were tested for statistical significance using the Kruskal-Wallis test. Correlations between different types of immune cells were determined using Spearman’s rank analysis. RESULTS: An increase in the rate of CD163(+) TAM infiltration was observed in mild and moderate epithelial dysplasia, which positively correlated with the rate of intraepithelial CD4(+) Th cell infiltration. Although CCR4(+) cells rarely infiltrated, CXCR3(+) and CCR5(+) cells were observed in these lesions. Cells positive for STAT1 and chemokine CXCL9, interferon- (IFN)-induced gene products, and pSTAT1 were also observed in the same lesions. Double immunofluorescence staining demonstrated that the cells that were positive for CD163 were also positive for STAT1. CONCLUSIONS: CD163(+) TAMs in oral premalignant lesions coexpress CD163 and STAT1, suggesting that the TAMs in oral premalignant lesions possess an M1 phenotype in a Th1-dominated micromilieu.